Pengaruh Mengunyah Buah Bengkuang (Pachyrhizus Erosus) Terhadap Skor Plak Pada Masyarakat Penderita Diabetes Mellitus di Kecamtan Simpang Tiga Kabupaten Pidie - Farrah Shafilla Azhari; Cut Aja Nuraskin (INDO PUBLISHING, 2026)
Background: People with diabetes mellitus are at risk of increased plaque accumulation due to oral health disorders. Jicama fruit (Pachyrhizus erosus) which is high in fiber and water is thought to help lower plaque scores through the self-cleansing effect. An initial survey on 10 people with diabetes mellitus showed that the plaque scores in 10 people with diabetes were in the bad category. Objective: To determine the effect of chewing Bengali fruit (Pachyrhizus Erosus) on a decrease in plaque scores in people with diabetes mellitus in Simpang Tiga District, Pidie Regency. Methods: Quantitative research with quasi experimental using pretest-posttest non-equivalent control group design was carried out on 05-20 May 2026 on 60 respondents from a population of 107 people selected using purposive sampling technique. Community dental hygiene data is assessed from plaque index (PHP) examination through clinical examination. Data analysis was conducted univariate and bivariate using the Nonparametric Wilcoxon Signed Rank Test. Results: Plaque scores after chewing jicama fruit decreased, with most of the respondents in the medium category (73%), as many as 17% were in the good category, and only 10% were still in the bad category. Test results. Wilcoxon which shows a p-value = 0.000 (p < 0.05). Conclusion: Chewing jicama fruit (Pachyrhizus erosus) has a significant effect on reducing plaque scores in people with Diabetes Mellitus. It is hoped that the public can consume jicama fruit as a supporting effort in helping to reduce the accumulation of dental plaque.